Infrastructure of the market economy - Walter Buhr (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
Infrastructure is the economic growth theory of the market economy. The missing comprehensive approach to infrastructure corresponds to the practiced neglect of the long-term policy objective of economic growth in the economic order of the German social market economy since its creation after World War II. Starting from Jochimsen's distinction of material, institutional and personal infrastructure, infrastructure policy as an indirect approach to economic growth policy is suggested. The main reason for this approach is our lack of knowledge about the process and results of future economic growth. With respect to the three categories of infrastructure selected aspects are discussed. Concerning material infrastructure now a definition is presented that can be integrated into a general definition of infrastructure. Regarding institutional infrastructure, after the presentation of relevant terms (rule, order, institution, organization) the analysis of important implications of institutional economics and its integration into constitutional economics follows. As to personal infrastructure, a quantitative component (population) and a qualitative component (human capital) are consistently distinguished and their determinants systematically elaborated. The determinants of human capital are education and learning from experience, research and development as the production of new knowledge or technological progress (inventions, innovations and diffusion of innovations). All of these considerations can be brought together in a general definition of the infrastructure of a market economy so far missing. Basically, this definition refers to a number of specifically characterized individual economic agents interacting under secure living conditions according to certain rules in the presence and the future. The analysis of infrastructure in a growing economy essentially leads to the result that personal infrastructure, especially human capital, is most important for structuring future economic growth. In the growth process, material and institutional infrastructure depend on personal infrastructure which in turn is influenced by material infrastructure (producing existence goods and services) and institutional infrastructure (e.g., population and education policy). Thus we discover infrastructure of the market economy to constitute a system in the sense of systems theory. Personal infrastructure of today may determine economic growth in the medium, long, and very long term, whereas institutional and material infrastructure indicate, as a rule, to have shorter reference periods. Due to its character, material infrastructure must be controlled and permanently maintained within the medium term. What is needed is a comprehensive and balanced time-oriented infrastructure policy approach, observing the natural environment, to settle the growth problems of the market economy. This approach would result in a revision of the present economic order of the social market economy.
Keywords: D78; J11; J24; O10; P11; 330; infrastructure; market economy; economic growth; existence goods; economic order; institution; population; human capital; infrastructure policy; Infrastruktur; Institutionelle Infrastruktur; Humankapital; Wirtschaftswachstum; Marktwirtschaft; Soziale Marktwirtschaft